Mechanotransduction Regulates Reprogramming Enhancement in Adherent 3D Keratocyte Cultures - Li, Shenyang; Ding, Chengcheng; Guo, Yonglong; Zhang, Yanan; Wang, Hao; Sun, Xihao; Zhang, Jun; Cui, Zekai; Chen, Jiansu (Frontiers in Bioengineering and Biotechnology, 2021)
Suspended spheroid culture using ultralow attachment plates (ULAPs) is reported to effect corneal fibroblast reprogramming. Polydimethylsiloxane (PDMS), with hydrophobic and soft substrate properties, facilitates adherent spheroid formation that promotes cellular physical reprogramming into stem-like cells without using transcription factors. However, it is still unknown whether the biophysical properties of PDMS have the same effect on adult human corneal keratocyte reprogramming. Here, PDMS and essential 8 (E8) medium were utilized to culture keratocyte spheroids and fibroblast spheroids, and the reprogramming results were compared. We provide insights into the probable mechanisms of the PDMS effect on spheroids. qPCR analysis showed that the expression of some stem cell marker genes (OCT4, NANOG, SOX2, KLF4, CMYC, ABCG2 and PAX6) was significantly greater in keratocyte spheroids than in fibroblast spheroids. The endogenous level of stemness transcription factors (OCT4, NANOG, SOX2, KLF4 and CMYC) was higher in keratocytes than in fibroblasts. Immunofluorescence staining revealed Klf4, Nanog, Sox2, ABCG2 and Pax6 were positively stained in adherent 3D spheroids but weakly or negatively stained in adherent 2D cells. Furthermore, OCT4, NANOG, SOX2, KLF4, HNK1, ABCG2 and PAX6 gene expression was significantly higher in adherent 3D spheroids than in adherent 2D cells. Meanwhile, SOX2, ABCG2 and PAX6 were more upregulated in adherent 3D spheroids than in suspended 3D spheroids. The RNA-seq analysis suggested that focal adhesion, regulation of the actin cytoskeleton, TGFβ/BMP and HIF-1 signaling pathways induced changes in mechanotransduction, the mesenchymal-to-epithelial transition and hypoxia, which might be responsible for the effect of PDMS on facilitating reprogramming. In conclusion, compared to corneal fibroblasts, keratocytes were more susceptible to reprogramming due to higher levels of endogenous stemness transcription factors. Spheroid culture of keratocytes using PDMS had a positive impact on promoting the expression of some stem cell markers. PDMS, as a substrate to form spheroids, was better able to promote reprogramming than ULAPs. These results indicated that the physiological cells and culture conditions herein are favorable to promote reprogramming. Therefore, adherent spheroid culture of keratocytes using PDMS is a promising strategy to more safely promote reprogramming, suggesting its potential application for developing clinical implants in tissue engineering and regenerative medicine.